A determination of the variation of soil moisture in three plots of soil during one month's growing period - Kiser, Orville M.; Praeger, Herman A. (My University, 1908)
Introduction: In choosing this work for our thesis we have intended to show the variation of soil moisture to a depth of four feet in three different plots; wheat, corn, and alfalfa, respectively, during the spring season from April 22 to May 21, ’08. The wheat and alfalfa made a good growth during this time while the corn was planted toward the end of the month and was coming up at the close of the experiment.
Citation: Kiser, Orville M. and Praeger, Herman A. A determination of the variation of soil moisture in three plots of soil during one month's growing period. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Soil; Agriculture; Wheat; Corn; Alfalfa; Graduating theses; Senior theses; Theses